2021
DOI: 10.1371/journal.pone.0256100
|View full text |Cite
|
Sign up to set email alerts
|

Repeated anodal high-definition transcranial direct current stimulation over the left dorsolateral prefrontal cortex in mild cognitive impairment patients increased regional homogeneity in multiple brain regions

Abstract: Transcranial direct current stimulation (tDCS) can improve cognitive function. However, it is not clear how high-definition tDCS (HD-tDCS) regulates the cognitive function and its neural mechanism, especially in individuals with mild cognitive impairment (MCI). This study aimed to examine whether HD-tDCS can modulate cognitive function in individuals with MCI and to determine whether the potential variety is related to spontaneous brain activity changes recorded by resting-state functional magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…A recent area of interest is represented by an implementation of tDCS technique, namely, high-definition tDCS (i.e., HD-tDCS), a novel approach that uses smaller electrodes whose configuration can be optimized for targeting specific brain regions ( 83 ). Such a technique offers some advantages then conventional method, as follows: (i) it can stimulate more precisely a target cortical region; (ii) aftereffects last at least 30 min longer than those obtained with conventional tDCS; (iii) it potentially reduces the likelihood of side effects; (iv) it determines less discomfort and improves applicability in the elderly ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent area of interest is represented by an implementation of tDCS technique, namely, high-definition tDCS (i.e., HD-tDCS), a novel approach that uses smaller electrodes whose configuration can be optimized for targeting specific brain regions ( 83 ). Such a technique offers some advantages then conventional method, as follows: (i) it can stimulate more precisely a target cortical region; (ii) aftereffects last at least 30 min longer than those obtained with conventional tDCS; (iii) it potentially reduces the likelihood of side effects; (iv) it determines less discomfort and improves applicability in the elderly ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial direct current stimulation is a non-invasive brain stimulation technique improving cognitive function in MCI. He et al (2021) found that fALFF values decreased significantly in the cerebellum of patients with MCI after receiving 10 transcranial direct current stimulation sessions. Accordingly, the decreased ALFF and fALFF in the cerebellum_9_R may contribute to cognitive and motor functional improvement in patients with MCI.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies have focused on patients with MCI whose cognitive function improved after treatment. He et.al ( He et al, 2021 ) used the transcranial direct current stimulation in patients with MCI and found that the fALFF and ReHo values changed in multiple areas following tDCS. Brain regions with significant decreases in fALFF values included the INS.R, Precuneus R, and Parietal Sup R, while the FFG.L and Angular R showed significantly increased fALFF values.…”
Section: Discussionmentioning
confidence: 99%
“…Frontal_Inf_Orb_L corresponded to the region of interest recommended by physicians for the clinical diagnosis of AD ( Jiang et al, 2015 ). Parietal_Sup_L may be associated with the underlying mechanism of its clinical effect, and it may play a role in the potential compensatory mechanism of mobilizing more regions to complete the function after a functional decline ( He et al, 2021 ). The Hippocampus_L and Hippocampus_R found in the AD-HC and EMCI-HC groups were reported as the pathogenic regions of AD.…”
Section: Discussionmentioning
confidence: 99%